Antiproliferative and antiviral activity of methanolic extracts from Sardinian Maltese Mushroom (Cynomorium coccineum L.). Issue 17 (19th August 2021) - Vascellari, Sarah; Zucca, Paolo; Perra, Daniela; Serra, Alessandra; Piras, Alessandra; Rescigno, Antonio
Abstract: Cynomorium coccineum is a non-photosynthetic plant that grows in Mediterranean countries and that is amply used in the traditional medicine. The aim of this study was to extend previous studies on the chemical and biological properties of C. coccineum, evaluating the potential antiviral and antiproliferative activity of the methanolic extract. The MTT assay was used for the in vitro cytotoxic studies against human cancer-derived cell lines, while both MTT and plaque reduction (PRT) methods were used to evaluate the potential inhibitory effect of the extract against a panel of mammal viruses. The results obtained showed no selective activity against any DNA and RNA virus but revealed an interesting antiproliferative activity against human leukaemia-derived cell lines. Graphical Abstract: UF0001